Understanding the Importance of Branding and Marketing in Small and Medium Enterprises - Dalvi, Neha (Digital Repository of Theses, 2026)
Available literature has studies done on marketing and branding in SMEs, but very few studies have been done to study the understanding of the importance SMEs have for branding and marketing. As per research and data available, SMEs have become an integral part of the economy and have contributed significantly towards the economic developments, but they are still lagging due to a lack of marketing and branding. All are aware of the various aspects of marketing and branding, but consider them as an expense; marketing and branding are the last factors to be considered in SMEs. This paper sheds light on understanding the importance of branding and marketing in small and medium enterprises, and this was done using the quantitative survey method through Google Forms. The obtained results are then thoroughly discussed, and recommendations for future research are given.